Spudcan deep penetration in multi-layered fine-grained soils. Issue 3 (1st September 2011) - Hossain, Muhammad Shazzad; Randolph, Mark F.; Saunier, Yvette N.
Abstract : This paper reports centrifuge modelling of spudcan foundations penetrating through multi-layered clays with interbedded stiff layers. Test specimens were prepared covering a range of normalised layer soil properties and geometry, mostly mimicking strength profiles from reported case histories, particularly those where punch-through failure occurred. Punch-through and rapid leg penetration (for strong-over-weak) and squeezing (for the reverse) were demonstrated by the penetration resistance profiles and associated soil failure mechanisms and provide a basis for developing design calculations. The results were compared directly with a field record of spudcan load–penetration response to evaluate their accuracy in predicting the shape of the spudcan resistance profile and final penetration depths, with excellent agreement obtained. A limiting squeezing depth of about 0·15 D was observed, increasing marginally with strength ratio, s ul / s uu, but with much greater depths where a soil plug was carried down from an upper strong layer with the spudcan. Where a stiff layer was underlain by a weaker layer, punch-through occurred with increasing severity for relatively lower strength ratio, s ul / s uu, and higher stronger layer thickness ratio, t / D . The severity of punch-through behaviour was reduced by the squeezing influence of another stiff layer within a short distance (less than about 0·6 D ).